2017
DOI: 10.1186/s12916-017-0904-7
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Now to Eliminate Repeat Unintended Pregnancy in Teenagers (INTERUPT): a systematic review of intervention effectiveness and cost-effectiveness, and qualitative and realist synthesis of implementation factors and user engagement

Abstract: BackgroundUnintended repeat conceptions can result in emotional, psychological and educational harm to young women, often with enduring implications for their life chances. This study aimed to identify which young women are at the greatest risk of repeat unintended pregnancies; which interventions are effective and cost-effective; and what are the barriers to and facilitators for the uptake of these interventions.MethodsWe conducted a mixed-methods systematic review which included meta-analysis, framework synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 67 publications
1
27
0
1
Order By: Relevance
“…This study and another systematic review highlighted the limited information on factors associated with repeat adolescent births in LMICs [21]. Poverty is associated with repeat adolescent pregnancies and births in both LMIC and high-income settings and has a high chance of reverse causality [20,21]. Poverty perhaps deprives the girl of the power to make decisions over further births, family planning use, access to abortion or by increasing chances of her deciding to complete her family size early due to lack of viable alternatives [20,21].…”
Section: Plos Onementioning
confidence: 93%
See 2 more Smart Citations
“…This study and another systematic review highlighted the limited information on factors associated with repeat adolescent births in LMICs [21]. Poverty is associated with repeat adolescent pregnancies and births in both LMIC and high-income settings and has a high chance of reverse causality [20,21]. Poverty perhaps deprives the girl of the power to make decisions over further births, family planning use, access to abortion or by increasing chances of her deciding to complete her family size early due to lack of viable alternatives [20,21].…”
Section: Plos Onementioning
confidence: 93%
“…Poverty is associated with repeat adolescent pregnancies and births in both LMIC and high-income settings and has a high chance of reverse causality [20,21]. Poverty perhaps deprives the girl of the power to make decisions over further births, family planning use, access to abortion or by increasing chances of her deciding to complete her family size early due to lack of viable alternatives [20,21]. Our study further supports that household poverty and young age at first birth appear to be major factors associated with repeat adolescent births.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, the inclusion of these studies fitted with our use of criterion sampling, an approach often used in qualitative evidence synthesis to 'construct a comprehensive understanding of all the studies that meet certain pre-determined criteria' (Suri, 2011, p.69). We aimed for inclusivity and therefore did not apply criteria for selecting only studies with the best evidence as outlined by Aslam et al (2017) who illustrate their use of the CART criteria (comprehensiveness, accuracy, relevance, timeliness) (Tennison, 2006), employed when there is a large number of studies.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Prompt access is of clinical significance, as the sooner EC is taken the more effective it is 1. Previous studies found that access was a barrier to EC use and that the longer opening hours, weekend openings and more accessible locations of pharmacies allowed most users to access EC within 24 hours;9 12 18 19 our study demonstrates that there remain barriers to access on Sunday. Possible reasons for this are fewer pharmacies being open and shorter opening times among those pharmacies that are open.…”
Section: Discussionmentioning
confidence: 46%